Evolution and Diversity of Listeria monocytogenes from Clinical and Food Samples in Shanghai, China - Zhang, Jianmin; Cao, Guojie; Xu, Xuebin; Allard, Marc; Li, Peng; Brown, Eric; Yang, Xiaowei; Pan, Haijian; Meng, Jianghong (Frontiers in Microbiology, 2016)
Listeria monocytogenes is a significant foodborne pathogen causing severe systemic infections in humans with high mortality rates. The objectives of this work were to establish a phylogenetic framework of L. monocytogenes from China and to investigate sequence diversity among different serotypes. We selected 17 L. monocytogenes strains recovered from patients and foods in China representing serotypes 1/2a, 1/2b, and 1/2c. Draft genome sequences were determined using Illumina MiSeq technique and associated protocols. Open reading frames were assigned using prokaryotic genome annotation pipeline by NCBI. Twenty-four published genomes were included for comparative genomic and phylogenetic analysis. More than 154,000 single nucleotide polymorphisms (SNPs) were identified from multiple genome alignment and used to reconstruct maximum likelihood phylogenetic tree. The 41 genomes were differentiated into lineages I and II, which consisted of 4 and 11 subgroups, respectively. A clinical strain from China (SHL009) contained significant SNP differences compared to the rest genomes, whereas clinical strain SHL001 shared most recent common ancestor with strain SHL017 from food. Moreover, clinical strains SHL004 and SHL015 clustered together with two strains (08-5578 and 08-5923) recovered from an outbreak in Canada. Partial sequences of a plasmid found in the Canadian strain were also present in SHL004. We investigated the presence of various genes and gene clusters associated with virulence and subgroup-specific genes, including internalins, L. monocytogenes pathogenicity islands (LIPIs), L. monocytogenes genomic islands (LGIs), stress survival islet 1 (SSI-1), and clustered regularly interspaced short palindromic repeats (CRISPR)/cas system. A novel genomic island, denoted as LGI-2 was identified. Comparative sequence analysis revealed differences among the L. monocytogenes strains related to virulence, survival abilities, and attributes against foreign genetic elements. L. monocytogenes from China were genetically diverse. Strains from clinical specimens and food related closely suggesting foodborne transmission of human listeriosis.